On economic efficiency of using lands in municipal district - E. N. Tsoraeva (Омский научный вестник: Серия "Общество. История. Современность")
Land use in accordance with its intended purpose is important part of land management, both in the municipality and in the country as a whole. The article considers the analysis of the state and dynamics of changes in the land fund, which allows to determine the prospects for land use. Determining the prospects for land use makes it possible to prepare in advance for future changes, to calculate the possible consequences of the actions applied in the present. And also allows you to solve the problems of efficient and rational use of land resources. Therefore, the study of the state of the land fund and the prospects for its use is relevant